Predicting outcomes with compounding comorbidities – Left-sided congenital diaphragmatic hernia complicated by pre-viable premature rupture of the membranes: A case report - Kate Landau; George Hardas; Gordon Thomas; Maria-Elisabeth Smet (Case Reports in Women's Health)
This case report describes the difficulty in predicting the outcomes for a fetus affected with both left-sided congenital diaphragmatic hernia and second-trimester pre-viable rupture of membranes. Despite the reserved prognosis at the time of diagnosis, a favourable outcome was obtained. The case highlights the relevance of established prognosticators such as the observed/expected lung/head ratio and also underscores the importance of balanced counselling and providing parents with realistic expectations and appropriate support.